(untitled) (The Research of Medical Science Review, 2025)
Objective: Optical Coherence Tomography (OCT) has been a useful tool in the diagnosis of glaucomatous and physiological cupping of the optic nerve head particularly in those patients with normal intraocular pressure (IOP). This study seeks to establish the ability of OCT to differentiate these two conditions in normal IOP individuals with particular reference to RNFL and GCC thickness. Method: This cross-sectional study was conducted in the Department of Ophthalmology at Peoples University of Medical and Health Sciences for Women, involving 60 patients: The number of participation by the students with GC was 30 while those with PC was also 30. The inclusion criteria were subjects aged between 18 and 60 years with suspect optic disc appearance, defined as the vertical cup-disc ratio of greater than 0.6 and untreated IOP less than 21 mmHg. The thickness of RNFL and GCC was determined by OCT using Nidek RS 3000. Results: There was a significant decrease in the average RNFL and GCC thicknesses of the GC group in comparison to the PC group. The mean RNFL thickness in the GC group was 91.8 ± 10.1 µm and for the SC group, it was 103.4 ± 9 µm. The mean reduction of epithelial thickness was 2 µm (p < 0. 001). Likewise, the overall mean of GCC thickness was 80.66 ± 16.86 µm in the GC group, which was lower than that of the PC group, which was 87.85 ± 12. 43 µm, (p < 0.001). In addition, the cup-to-disc ratio was larger in GC (0. 71 ± 0. 05) than in PC (0. 63 ± 0. 04) (p < 0. 001). Conclusion: In patients with normal IOP this paper argues that OCT helps distinguish between physiological and glaucomatous cupping and hence helps in diagnosis and management